'COLUMBANUS WORE A SINGLE COWL, NOT A DOUBLE ONE': THE VITA DEICOLI AND THE LEGACY OF COLUMBANIAN MONASTICISM AT THE TURN OF THE FIRST MILLENNIUM. (2021) - VANDERPUTTEN, STEVEN
Abstract : This article analyses the Life of St. Deicolus of Lure, a monastery in the Alsace region of east France, written by the cleric Theodoric in the 970s or 980s. It argues that the text contains a notable amount of information on the existence, methodology, and limitations of an ill-understood aspect of monastic integration around the year 1000. Relying on an analysis of the narrative's second prologue as well as scattered comments elsewhere in the text, it reconstructs three phenomena. The first is attempts to (re-)establish a Luxeuil-centered imagined community of institutions with a shared Columbanian legacy through the creation and circulation of hagiographic narratives. A second is the co-creation across institutional boundaries of texts and manuscripts that were designed to facilitate these integration attempts. And the third phenomenon is the limits of this integration effort, which did not tempt those involved to propose the establishment of a distinct 'neo-Columbanian' observance. As such, the Life represents an attempt to reconcile the legacy of Columbanus and his real or alleged followers as celebrated at late tenth-century Luxeuil and Lure with a contemporary understanding of reformed Benedictine identity.